Beyond the various contrivances by which orchids are pollinated: global patterns in orchid pollination biology - Ackerman, James D; Phillips, Ryan D; Tremblay, Raymond L; Karremans, Adam; Reiter, Noushka; Peter, Craig I; Bogarín, Diego; Pérez-Escobar, Oscar A; Liu, Hong (Botanical journal of the Linnean Society, 2023)
Abstract Orchidaceae show remarkable diversity in pollination strategies, but how these strategies vary globally is not entirely clear. To identify regions and taxa that are data-rich and lend themselves to rigorous analyses or are data-poor and need attention, we introduce a global database of orchid reproductive biology. Our database contains > 2900 species representing all orchid subfamilies and 23 of 24 tribes. We tabulated information on habit, breeding systems, means of pollinator attraction and the identity of pollinators. Patterns of reproductive biology by habit, geography and taxonomy are presented graphically and analysed statistically. On the basis of our database, most orchid species sampled are pollinator dependent (76%) and self-compatible (88%). Pollinator attraction based on rewards occurs in 54% of the species, whereas 46% use some means of deceit. Orchids generally have highly specific pollinator interactions (median number of pollinator species = 1). Nonetheless, on average, specificity is lower for species offering rewards, occurring in multiple continental regions or Northern America (as defined by the Taxonomic Database Working Group Level 1 regions). Although our database reveals impressive knowledge gains, extensive gaps in basic observations of orchid reproductive biology exist, particularly in tropical regions and diverse lineages of fly-pollinated species. The database is expected to facilitate targeted studies, further elucidating the ecological and evolutionary drivers of orchid diversity.